KEEFEKTIFAN PELATIHAN MENTORING TERHADAP PERSEPSI MAHASISWA TENTANG PERAN PEMBIMBING AKADEMIK PADA MAHASISWA PROFESI NERS UNIVERSITAS MUHAMMADIYAH SEMARANG - Tri Nurhidayati; Yuni Armiyati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2012)
Background. Clinical components are very important in the curriculum of nursingeducation. One of the barriers in learning is psychological stress caused by manytasks, financial issues, exams, and lecturers. To get success in the education ofprofession, nursing students can be supported by an academic supervisor. Studentswho had problems should meet with an academic supervisor, but the guidance couldnot come well.Objective. This study aimed to find out the effectiveness of mentoring training ofacademic counselors on student’s perceptions about the role of academic counselorsof nursing profession of Universitas Muhammadiyah Semarang.Methods. This study used a quasi experimental and the design of this study was pretest and post test design with control group.Results. Hypothesis test results indicated that the p value was 0.00 at an alpha of0.05, so that the value of p value was less than the alpha value. The role ofsupervision by the academic counselors who received mentoring training was moreeffective than those without the training.Conclusion. The role of supervision by the academic counselors who receivedmentoring training was more effective than those without the training. It isrecommended that academic counselors should continually develop themselves andmaintain quality.